2004
DOI: 10.2139/ssrn.581701
|View full text |Cite
|
Sign up to set email alerts
|

The Incentive Effects of Higher Education Subsidies on Student Effort

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
1
7
0
1
Order By: Relevance
“…In turn, this would simply provide less incentives to accumulate human capital, not more. This intuition complements a recent calibration exercise proposed by Sahin (2003) who finds that subsidizing tuition increases enrollment rates but reduces student effort, hence human capital accumulation. 13 The failure of subsidies to improve educational outcomes is something our model shares with "pure signaling" models of education, i.e.…”
Section: Schooling Costs and The Remuneration Of Skillsupporting
confidence: 79%
See 1 more Smart Citation
“…In turn, this would simply provide less incentives to accumulate human capital, not more. This intuition complements a recent calibration exercise proposed by Sahin (2003) who finds that subsidizing tuition increases enrollment rates but reduces student effort, hence human capital accumulation. 13 The failure of subsidies to improve educational outcomes is something our model shares with "pure signaling" models of education, i.e.…”
Section: Schooling Costs and The Remuneration Of Skillsupporting
confidence: 79%
“…3 As in our paper, human capital accumulation in such models suffers when incentives to student achievement are weak. For example see the studies by Betts (1998) and Sahin (2003) on the economic impact of education standards and financing. What sets our model apart is the root of productivity disparities.…”
Section: Introductionmentioning
confidence: 99%
“…However, in our study we found no age-dependent effect of tuition fees on duration of studies or dropout rate, respectively. Though one might argue that tuition fees in Cologne have been rather low other studies have shown that public share aiming at reducing financial burden of students was accompanied by even prolonged duration of studies and lower performance of students [ 16 ], [ 22 ]. One can speculate, that recognizing medical studies as a course of studies with very high prestige might have prompted students to successfully finish “at all costs”.…”
Section: Discussionmentioning
confidence: 99%
“…Sahin (2004) untersucht den Effekt von Studiengebühren auf die Anstrengung von Studierenden. In einem auf die USA kalibrierten Modell zeigt er, dass das Bemühen von Studierenden, auch der stark motivierten, mit höherer finanzieller Förderung zurückgeht.…”
Section: These 2: Studiengebühren Führen Zu Effizienteren Studieneunclassified